Transformation Tradition Toba Batak Traditional Marriage in Perspective Ethnoscience - Lubis, Suriati; Hariyadi, Bambang; Zurweni, Zurweni; Haryanto, Haryanto (Journal of English Language and Education, 2025)
This study aims to examine and describe customs of marriage in the Toba Batak people, in particular the stages of implementation, values contained in the culture, as well as changes that occur as a consequence of the influence of modernization. The methods used is a qualitative approach with data collection techniques through observation, in-depth interviews, and literature study. Research results show that the customs of Toba Batak weddings consist of a number of important stages, such as mangarisik, marhata sinamot, pamasu-masuon, and the party show. Each stage contains strong social, religious, and kinship values, as well as confirms the social structure of the Toba Batak people, especially the clan system. However, modernization and shifts in society cause a number of customary stages to be simplified or abandoned. This research concludes that although the customs of Toba Batak marriage are still preserved, there is a transformation in meaning and practice as a form of adaptation to contemporary socio-cultural dynamics.